Gender and action films 1980-2000 : beauty in motion - Gerrard, Steven; Middlemost, Renée (Emerald studies in popular culture and gender., 2022)
Sylvester Stallone's action thriller, First Blood, hit cinema screens in 1982, leading to the cementing of what can be called the Action Movie Canon. With films like Die Hard, Under Siege and Total Recall pioneering post-millennial Action Movies such as Tomb Raider, The Bourne Identity and Atomic Blonde, there is a clear trajectorial line showing that the Action Movie has radically altered to incorporate much more complex portrayals of both 'hero' and 'heroine': the Action Movie Hero. Examining the changing face of Action Movies and their representations of gender since the release of First Blood, Gender and Action Films 1980-2000 examines masculinity and anxiety through subjects ranging from gender spaces in action films to the buddy cop film. From transformative femininity, motherhood and machoism, action women in contemporary Colombian cinema, reconsidering gender in Jurassic Park, to gender, politics and 80s action - the chapters dive into everything from sword-playing and gun-shooting women and rainbow-coloured riots on Hollywood boulevard. Gender and Action Films 1980-2000 offers a comprehensive insight into the intertwined concepts of gender and action, and how their portrayal developed in the Action Movie genre during the final two decades of the twentieth century. A necessity for academics, students and lovers of film and media and those interested in gender studies.